Islamic Party Political Communication Strategy in the Digital Era - Dharta, Firdaus Yuni; Khan, Jamil; Ali, Zara (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2025)
In the digital era, political communication strategies have evolved to include social media, digital platforms, and online engagement, significantly affecting how political parties, particularly Islamic parties, reach and interact with voters. This study examines the political communication strategies employed by Islamic parties in the digital space, focusing on their use of social media, digital campaigns, and online engagement to connect with Muslim voters. The research aims to explore how Islamic political parties adapt their message and strategy to the changing landscape of digital media. A qualitative research design was used, combining interviews with political communication experts, survey data from voters, and content analysis of the digital campaigns of major Islamic political parties. The findings show that Islamic political parties leverage social media platforms such as Twitter, Facebook, and Instagram to spread their messages, enhance political participation, and increase voter engagement. However, challenges remain in ensuring authenticity and avoiding the risk of misrepresentation in the digital space. The study concludes that while Islamic parties are successfully adapting to the digital era, they must continue to innovate and ensure their messages resonate with younger, digitally-savvy voters. Further research is needed on the long-term effectiveness of digital strategies in Islamic political campaigns.